Healthcare professionals' perceptions of their work with patients of working age with heart failure. (September 2018) - Frank, Catharina; Lindbäck, Camilla; Takman, Christina; Nordgren, Lena
There is a lack of knowledge about healthcare professionals' perspectives on rehabilitation in relation to heart failure. Still, collaboration between different professionals can impact patients. The purpose of this study was to describe healthcare professionals' perceptions of their work with patients of working age with heart failure. The sample population consisted of six nurses, one physiotherapist and one cardiologist. One individual interview and two focus-group interviews were conducted. The interviews were analyzed using qualitative content analysis. Three descriptive categories were constructed: 'the impact of heart failure on patients' life situations', 'heart failure service', and 'patients' process of returning to work'. To support patients, healthcare professionals need to find ways to combine patients' personal needs with protocol-driven care.